2006
DOI: 10.1080/00016350500331096
|View full text |Cite
|
Sign up to set email alerts
|

Anin vitromicrobial-based model for studying caries-preventive agents

Abstract: In conclusion, our in vitro system is suitable for testing potential caries-preventive agents in a reproducible way by using whole tooth samples and offers full access together with the possibility of manipulating the specimens during operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Experiences with the cariogenity of the selected kind of S. mutans have been reported previously [9,13,33,46]. As a consequence, in the chosen set up, distinct demineralization was evident already after short incubation times.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Experiences with the cariogenity of the selected kind of S. mutans have been reported previously [9,13,33,46]. As a consequence, in the chosen set up, distinct demineralization was evident already after short incubation times.…”
Section: Discussionmentioning
confidence: 86%
“…Due to ethical problems with experimental clinical studies, in vitro models have the potential to elucidate fundamental aspects of caries processes by simulating the human oral microcosm [12,[23][24][25][26][27][28][29][30][31][32][33]. Main advantage here is that artificially proliferated plaque may be incubated with particularly interesting bacteria [14,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the lectin-mediated binding specificities of caries-inducing microorganisms are not very well characterized yet, studies revealed that a high molecular mass cranberry constituent was capable of reducing mutans streptococci level in saliva and effectively inhibiting in vitro adhesion to hydroxyapatite [22,23]. Furthermore, studies in an artificial mouth model showed a caries-preventive effect of an experimental glycan solution prepared by hydrolysis of porcine gastric mucine on natural teeth [24]. Early adhesion experiments by Gibbons and Qureshi revealed that the adhesion of different S. mutans serotypes to saliva-coated hydroxyapatite could be inhibited by galactose and melibiose (6-α-D-galactosyl-glucose) but not by lactose [25].…”
Section: Discussionmentioning
confidence: 97%